Infrastructure for Smart City through a Secured Intelligent Structure for IoT Interoperability - Latha, Challa Madhavi; Sharma, Hemant; Indracanti, Meera; Tegegne, Habtamu (Indian Journal of Computer Science, 2020)
The present paper is associated with IoT interoperability which will become a significant issue over the next couple of years. This issue consists of intelligent infrastructures, architectures, platforms and designs; IoT device privacy and security awareness, and IoT interoperability real time application in a smart city. A city is a large place for human ecology which offers facilities, services, and opportunities to natives. Rapid growth of population is posing a lot of challenges for infrastructures of cities and delivery of services. City life can be modernized by innovative strategies and planning infrastructure. Now-a-days, cities are transforming into smart cities by enhancing the performance and quality of services by applying smart objects, digitalization, and intelligent advanced techniques. The present study concentrates on all possible dimensions of the city which can make a city smarter. Moreover, the basic infrastructure of a smart city has been proposed in all required domains. Furthermore, a Secured Intelligent Structure for IoT Interoperability (SISII) framework has been proposed to suggest solutions for the smart city. Three functional areas viz. initiation to plan the infrastructure, development of core infrastructure, and distributed infrastructure have been discussed in SISII framework to demonstrate a smart city.